Rol de la mujer en las elecciones seccionales en el Gobierno Autónomo Descentralizado de la parroquia Yangana, cantón Loja, año 2019 - Delgado Mendoza, Yuddy Elizabeth (2023)
The representation of women in political as candidates is essential for modern democracy and to fight against machismo and make their rights heard. Thus, women face enormous challenges in society and political life where the male gender has led for years. Thus, the general purpose was focused on determining the role of women in the sectional elections in the decentralized autonomous government of the Yangana parish of the canton of Loja in 2019; as well as identifying the application of women's rights and the acceptance of the electorate in the sectional lessons. Therefore, to fulfill the objectives, action research methodology was applied. The methods used were deductive, inductive and analytical. This helped with the analysis of general information, through documentary review, and the local reality. The techniques used were citizen surveys, interviews with women who participated in 2019 for the parish council. In this way it was possible to determine that, despite the years, women's role in a candidacy is to fill a list. This is to help the party financially with the campaign. For which a proposal was made to promote women's political participation in sectional elections in the Yangana parish. Finally, conclusions and recommendations were developed.